SUSTAINABILITY MEASURES FOR INDUSTRIAL PROCESSES: WITH A FOCUS ON ALTERNATIVE ENERGY- BIOMASS (JÓVENES EN LA CIENCIA, 2017)
Nowadays, there is a growing awareness worldwide about the use and consumption of energy, which has generated the need to assess and monitor the amount of energy needed to generate products and services. Energy efficiency indicators are an important tool to analyze the interactions between economic and human activity, energy consumption and emissions of carbon dioxide (CO2). This paper deals with a detailed analysis of the factors of energy efficiency at a national level, the differences between energy and exergy addition to proposing the exegetical analysis as an additional index that will identify energy losses (irreversibilities) in a system. From the results of measurement of energy and exergy efficiencies a simulation of a relevant case study was performed in ASPEN HYSYS simulation.
Keywords: Array; Array; Array; Array; Array; Array